1999
DOI: 10.1111/j.1748-0361.1999.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Hospital Closure on Small Rural Counties, 1984 to 1988: Demonstration of a Comparative Analysis Approach

Abstract: Hospital closure in a rural community may affect the locale's economic prospects as well as the health of its residents. Studies of economic effects have primarily relied on modeling techniques rather than observation of actual change. This study demonstrates the use of a comparative analysis approach for estimating the economic effects of hospital closure on small rural counties. The experiences of 103 small rural counties at which a hospital closed between 1984 and 1988 was compared with a matched group of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
17
2
Order By: Relevance
“…The difficulty, of course, is that the counterfactual is not observed for counties that do not experience a closure; this must be estimated. If hospital closures are not correlated with unobserved factors, then one could estimate models using, for example, a propensity‐score approach as used by Probst et al (1999). An alternative method (Stensland et al 2002), is to use a longitudinal approach and compare the outcomes for closure counties with the outcomes of nonclosure counties (used as the estimate of the counterfactual).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty, of course, is that the counterfactual is not observed for counties that do not experience a closure; this must be estimated. If hospital closures are not correlated with unobserved factors, then one could estimate models using, for example, a propensity‐score approach as used by Probst et al (1999). An alternative method (Stensland et al 2002), is to use a longitudinal approach and compare the outcomes for closure counties with the outcomes of nonclosure counties (used as the estimate of the counterfactual).…”
Section: Methodsmentioning
confidence: 99%
“…Five economic indicators were examined for trends and none were found to have had a statistically significant change following closure of the hospital. Similarly, Probst et al (1999) compared economic indicators in closure communities to a control group of nonclosure communities and failed to find a statistically significant difference in income trends in the closure counties relative to the comparison counties. Stensland et al (2002) examined the effect of 42 hospital closures in rural Appalachian communities and concluded that the closure had no effect on short‐term or long‐term economic growth of those areas.…”
mentioning
confidence: 99%
“…A South Carolina study found that National Health Service Corps physician alumni, in addition to serving rural and racial/ethnic minority populations, 83 generated an estimated $15 million in annual billings (in 1998) per county in rural HPSA counties. 84 Conversely, the loss of health care providers as employers within small rural counties has significant detrimental economic consequences. 85 …”
Section: Interdisciplinary and Interinstitutional Cooperationmentioning
confidence: 99%
“…Research has already shown that the closure of rural hospitals, often a major employer, can have significant economic effects on the community. 50 Short-run studies should be done at the state level to document how cutbacks in Medicaid, or of differential funding for elementary and secondary education in rural minority and poverty counties, affect health outcomes. On the positive side, research needs to identify, document, and replicate examples of successful collaboration between health care institutions and economic development systems.…”
Section: Discussionmentioning
confidence: 99%